Physicochemical approach of moisture damage susceptibility of binder-aggregate interfaces - Baldi-Sevilla, Alejandra (2025)
Moisture damage is one of the most severe distresses in pavements.  Among the causes of moisture damage is the poor quality of the binder-aggregate interface formed during mixing. The weakness of the interface might be due to a poor interaction between materials, which increases the susceptibility of binder of being removed from the aggregate surface by water. In this study, the quality of the binder-aggregate interface was approached by means of surface energy measurements of several binder-aggregate combinations. Two different aggregate sources were investigated: a limestone and a gravel, which were combined with three  asphalt binders: a diatoms-modified binder, a nanosilica-modified binder and neat binder as control. The proposed combinations were evaluated by means of physicochemical indicators related to moisture damage, such as work of adhesion, work of debonding and energy ratio. It was found that the quality of the interface is highly related to the aggregate source. Furthermore, several anti-strip additives were evaluated in terms of reduction of water susceptibility of the combinations and it was observed that their efficiency is dependent on the aggregate source with which the modified binder is combined. In summary, various parameters associated to interfaces can be obtained from surface energy measurements of binders and aggregates. This technique allows the physicochemical evaluation of binders and aggregates and the information obtained might be used as criteria for appropriate selection of water-resistant materials.